A NEW PERSPECTIVE ON THE AGE AND GEOLOGICAL STRUCTURE OF THE NEOGENE VERTEBRATE LOCALITY KHYARGAS NUUR 2 (NORTHWESTERN MONGOLIA) - A. V. Sizov; M. V. Sotnikova; S. A. Sokolov; A. A. Yakimov; A. S. Tesakov; I. A. Vislobokova; N. V. Zelenkov; A. N. Simakova; K. I. Yushin; Ts. Batsaikhan (Геодинамика и тектонофизика, 2024)
The Great Lakes Depression in northwestern Mongolia contains widespread Late Neogene continental deposits, reaching thicknesses of several hundred metres. The Late Neogene Khyargas Nuur formation (also known as the Khirgis-Nur formation) has a significant biostratigraphic value for Central Asia, as it encompasses a unique palaeontological record and has a wide geographical distribution in the region. The stratotype of this formation was described in the Khyargas Nuur 2 (=Khirgis-Nur-2) section on the northern shore of Khyargas Lake. Bio- and magnetostratigraphic studies conducted in the 1970s and 1980s identified the Miocene-Pliocene boundary (corresponding to the Turolian and Ruscinian biochrons) within Unit A, or the Lower Khyargas Nuur subformation. This study aims to refine the age and stratigraphic subdivisions of the Khyargas Nuur formation in light of new data. Examination of the geology of the Lower Khyargas Nuur Subformation stratotype, along with a revision of the associated mammalian assemblage (carnivores, ungulates, and rodents), supports the conclusion that this faunal complex corresponds to the Late Turolian (MN13) of the continental biochronological scale, thus assigning this section to the terminal Miocene. These findings provide new insights into the geological history of the Great Lakes Depression and the faunal history of Central Asia.